2016
DOI: 10.5539/gjhs.v8n10p127
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Physical Activity in Women with Polycystic Ovary Syndrome in Comparison to Eumenorrheic Non Hirsute Women

Abstract: Polycystic Ovary Syndrome is the most common endocrinopathy in women of reproductive age. Although physical activity and weight loss has been proposed as the first line management in patients with PCOS, studies on physical activity in patients with PCOS are limited. The aims of this study were to compare levels of physical activity and its related factors between women with polycystic ovary syndrome and eumenorrheic non hirsute women. We compared the physical activity of our study group using the international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Although significantly difference in two domains of HRQoL including emotional disturbance and menstrual predictability between physical activity groups was found, physical activity did not significantly predict the total and domains of HRQoL after adjusting for sedentary behaviors and other related variables. In fact, most (91.5%) of participants had physical inactivity or moderate intensity of physical activity in this study, which indicated a lower level of physical active in this group and was comparable to study by Farnaz et al (90.8%) [ 49 ]. Greenwood et al found that vigorous but not moderate activity is associated with reduced odds of the metabolic syndrome in women with PCOS [ 50 ].…”
Section: Discussionsupporting
confidence: 89%
“…Although significantly difference in two domains of HRQoL including emotional disturbance and menstrual predictability between physical activity groups was found, physical activity did not significantly predict the total and domains of HRQoL after adjusting for sedentary behaviors and other related variables. In fact, most (91.5%) of participants had physical inactivity or moderate intensity of physical activity in this study, which indicated a lower level of physical active in this group and was comparable to study by Farnaz et al (90.8%) [ 49 ]. Greenwood et al found that vigorous but not moderate activity is associated with reduced odds of the metabolic syndrome in women with PCOS [ 50 ].…”
Section: Discussionsupporting
confidence: 89%
“…These exercise regimens were followed over 36 sessions over 12 weeks. For baseline assessment, a laboratory test for total serum testosterone levels was performed by taking the participants’ blood samples, the chief examiner took skinfold measurements for BF% using a body caliper, and an international physical activity questionnaire for physical activity measurement was filled out by the participants [ 16 ]. All outcome measures were reassessed at the end of the last intervention session (post intervention).…”
Section: Methodsmentioning
confidence: 99%
“…There are limited studies on PA among women with PCOS, and the results are inconsistent. In some studies, the level of PA among these women was reported to be less than healthy women, while other studies did not show a significant difference in PA between women with and without PCOS (9). The obstacles such as fatigue, lack of time, lack of self-confidence to maintain PA, fear of injury, and physical limitations have reported for doing PA (8).…”
Section: Introductionmentioning
confidence: 99%